Unraveling the Complex Landscape of MDR-TB: A Comprehensive Retrospective Study on Treatment History, Demographics, and Drug Resistance Patterns in District Swat - Jamal, Khalid; Khalid, Muhammad; Ahad, Abdul; Hassan, Azan; Khan, Shah Hassan; Burhanullah; Samid Ur Rehman (Indus Journal of Bioscience Research, 2024)
Therapy for tuberculosis (TB) involves the application of first-line medicines (FLDs), such as isoniazid (INH), rifampicin (RIF), pyrazinamide (PZA), ethambutol (EMB), and streptomycin (SM). Second-line medications (SLDs) are employed if the first-line therapy fails or the bacteria develop resistance to the FLDs. The present research set out to evaluate the drug-resistant tuberculosis prevalence and determine the drug-resistant patterns in District Swat. Materials and Methods This was an observational, hospital-based, retrospective research of previously diagnosed cases of all Drug sensitive TB (DS-TB), MDR-TB, and XDR-TB patients provided by the Programmatic Management of Drug-Resistant TB (PMDT) Saidu Group of Teaching Hospital, Swat from January 2015 to December 2019. There were 15,567 isolates of DS-TB and MDR-TB in all from the research. The data was analyzed applying the statistical software SPSS version 25 (SPSS Inc., Chicago, IL, USA) and Microsoft Excel (Microsoft Office Professional Plus 2016). Results According to the results, between January 2014 and December 2019, a total of 15,567 patients were registered from 13 District SWAT centers, comprising 15356 (98.64%) new cases and 211 (1.36%) re-treatment cases with known age and sex. The proportion of TB in the male population (51.9%) was higher than in the female population (48.0 %). Overall treatment success rate (TSR) for PBC cases was (3097) 93.9%. Conclusion Finding the baseline susceptibility to first- and second-line medications as soon as possible is necessary to prevent developed drug resistance and unfavorable outcomes, according to the investigation’s conclusion